Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) pada Jenjang Sekolah Dasar - Endang Sri Maruti; Ibadullah Malawi; Muhammad Hanif; Sri Budyartati; Nur Huda; Wahyu Kusuma; Moh. Khoironi (Abdimas Mandalika, 2023)
Abstract:  Project assistance to strengthen the profile of Pancasila students at elementary school level is one of the efforts to realize the implementation of an independent curriculum. The aim of this program is to improve the P5 implementation process in independent curriculum pilot schools, so that the project can run according to the actual concept. This program was implemented in November 2022 at SDN 03 Taman Kota Madiun. The results of the activity show that there is an increase in the quality of P5 implementation in schools that have implemented the independent curriculum.Abstrak: Tujuan program ini adalah untuk memperbaiki proses pelaksanaan proyek penguatan profil pelajar Pancasila (P5) pada sekolah perintis kurikulum merdeka, sehingga proyek dapat berjalan sesuai dengan konsep yang sebenarnya. Pendampingan projek penguatan profil pelajar Pancasila pada sekolah tingkat dasar merupakan salah satu upaya untuk mewujudkan implementasi kurikulum merdeka. Program ini dilaksanakan pada bulan November 2022 di SDN 03 Taman Kota Madiun secara luring. Hasil kegiatan program ini menunjukkan bahwa setelah pendampingan dilakukan, terdapat peningkatan kualitas pelaksanaan P5 pada sekolah yang telah menerapkan kurikulum merdeka.